Physical activity and sedentary lifestyle: Impact on health and quality of life of older people - Francisco Salinas Martínez; Armando Cocca; Kamal Mohamed; Jesús Viciana Ramírez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2010)
We analyzed the current status of the elderly in relation to physical activity and sedentary, the latter now become a major source of threat to public health in the European and American countries. We report the negative effects of physical inactivity on cardiovascular parameters, diabetes, depression and cancer, among others. We show the benefits of physical activity (a key tool to solve the problems of the sedentary lifestyle) for the health of this group of the population while we study the reasons why older people attend physical activity programs. Finally, we provide a number of conclusions.